PENGARUH PEMAHAMAN PERPAJAKAN DAN KEMUDAHAN DALAM MEMBAYAR PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM YANG TERDAFTAR DI KPP PRATAMA BATU - Rara Nur Aliefia Alfiyani; Noor Shodiq Askandar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of tax understanding and convenience in paying tax of UMKM taxpayer compliance. Researchers determine UMKM taxpayers who are active and registered at the pratama Batu Tax Service Office as the population. Meanwhile, the researcher used the slovin formula in determining the sample with a total of 99 respondents. The research method used in quantitative research with primary data analysis was carried out by multiple linear regression analysis using SPSS. The result of this study indicate that tax understanding and convenience in paying tax have significant effect on UMKM taxpayer compliance either partially or simultaneously.Keywords : taxpayers, slovin formula, multiple linear regression